2016
DOI: 10.1681/asn.2014121208
|View full text |Cite
|
Sign up to set email alerts
|

CKD Stimulates Muscle Protein Loss Via Rho-associated Protein Kinase 1 Activation

Abstract: In patients with CKD, muscle wasting is common and is associated with morbidity and mortality. Mechanisms leading to loss of muscle proteins include insulin resistance, which suppresses Akt activity and thus stimulates protein degradation via the ubiquitin-proteasome system. However, the specific factors controlling CKDinduced suppression of Akt activity in muscle remain undefined. In mice with CKD, the reduction in Akt activity in muscle exceeded the decrease in upstream insulin receptor substrate-1-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…For example, we reported that the phosphatase PTEN inhibition protects muscle wasting in CKD mice [3;4]; knockdown of protein phosphatase 2C-alpha (PP2Cα) protects angiotensin II-induced muscle wasting [37]. In the present study, we demonstrated a novel nuclear phosphatase, SCP4, which regulates muscle protein degradation by preventing FoxO1/3a nuclear translocation and activity.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…For example, we reported that the phosphatase PTEN inhibition protects muscle wasting in CKD mice [3;4]; knockdown of protein phosphatase 2C-alpha (PP2Cα) protects angiotensin II-induced muscle wasting [37]. In the present study, we demonstrated a novel nuclear phosphatase, SCP4, which regulates muscle protein degradation by preventing FoxO1/3a nuclear translocation and activity.…”
Section: Discussionmentioning
confidence: 53%
“…After being fixed with 4% formaldehyde, the frozen tibialis anterior muscles’ sections (5 μm) were subjected to immunostaining or immunohistochemistry as described [3]. For measuring myofiber diameter, C2C12 myotubes were transfected with adenovirus bearing GFP for 24 h to outline cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…) or of PKB activity (Peng et al. ). It was shown that miR‐148b is involved in the PKB pathway by downregulation of ErbB3 receptor (Bischoff et al.…”
Section: Discussionmentioning
confidence: 99%
“…2 Potential stimuli of muscle wasting in CKD include impaired insulin/IGF-1 signalling, excess glucocorticoids production, up-regulation of myostatin expression and systemic inflammation. 3,4 Unfortunately, the development of therapeutic interventions that block muscle wasting is still at initial stages. 5,6 We examined whether a herbal compound, ursolic acid, will block muscle wasting by inhibiting myostatin expression and inflammatory pathways.…”
Section: Introductionmentioning
confidence: 99%